Review of the world Monoctonina Mackauer 1961 (Hymenoptera, Braconidae, Aphidiinae): key for their identification and descriptions of five new species - Čkrkić, Jelisaveta; Petrović, Andjeljko; Kocić, Korana; Kavallieratos, Nickolas G.; Hebert, Paul D.n.; Tomanović, Željko (Zootaxa, 2019)
The subtribe Monoctonina has long been overlooked when it comes to morphological studies, probably due to the low economic importance of its members. Mainly distributed in high montane areas and forest ecosystems, species of Monoctonina are not often found in large populations and do not parasitize pests of cultivated plants. Our research uncovered five new species belonging to this subtribe (Monoctonus brachyradius sp. n., M. canadensis sp. n., M. inexpectatus sp. n., M. luteus sp. n., and M. parvipalpus sp. n.). We also redescribe species originally described over a century ago, and discuss the utility of certain morphological characters, as well as status of some species within Monoctonina.